FAKTOR – FAKTOR.YANG BERPENGARUH TERHADAP MINAT MENGGUNAKAN APLIKASI BERBASIS FINANCIAL TECHNOLOGY (FINTECH) DI DESA BARENGKOK, DESA PABANGBON DAN DESA LEUWIMEKAR KECAMATAN LEUWILIANG KABUPATEN BOGOR - Hedriawan, Adjriel; Trihantana, Rully; Anwar, Miftakhul (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2023)
This research examines the factors of social influence, benefits, and security, in influencing or not influencing interest in using financial technology-based applications. This research uses quantitative methods. The population in this study were people in Barengkok Village, Pabangbon Village and Leuwimekar Village. The three villages are in Leuwiliang District, Bogor Regency. The sampling technique uses the Purposive Sampling method. The data used is primary data, namely using a questionnaire with a sample of 300 people. The results of this research show that social influence, benefits and security factors partially and simultaneously influence interest in using financial technology applications